Implementation Method Amtsilati to Improving Abilities Great of Reading at Islamic Boarding School Mathooli’ul Anwar | Implementasi Metode Amtsilati untuk Meningkatkan Kemampuan Maharah Qiro’ah di Pondok Pesantren Mathooli’ul Anwar - Mughniatur Rosidah; Umi Nur Azizah; Ade Destri Deviana (An-nahdloh : Journal of Arabic Teaching, 2023)
This study presents the implementation of Amtsilati methods in Islamic Boarding School Mathooli’ul Anwar Kotagajah area to improve the skills of Maharah Qiro'ah. The purpose of this study is to describe how the Amtsilati method can be used to improve the skills of Maharoh Qiro'ah in the area of ​​Amtsilati in Islamic Boarding School Mathooli’ul Anwar Kotagajah. This study is a descriptive research using qualitative methods. The subjects of this study included educators, dormitory administrators, and students. The data collection techniques used included interviews, observations and records. Collected data is analyzed in several steps: viewing data, data reduction, and conclusions. The results of this study show that the application of the Amsilati method in the Amsilati dormitory in the Islamic Boarding School Mathooli’ul Anwar Kotagajah area can improve the abilities of the Maharah Qiro'ah. Applications The Amsilati method is identical to its application, except that there is a The application of Amtsilati is not much different in DarulFalah Islamic Boarding School, Jepara. learning process and The Amsilati method by Islamic boarding school Mathooli’ul Anwar Kotagajah starts with reading Khulashoh, Hadloroh, Qoidah, then explain, argue with some Example, Synchronization and Evaluation.